High Dose Methylprednisolone: Effective in Pregnancy Associated Post-splenectomy Refractory Chronic Immune Thrombocytopenic Purpura - Singh, A; Solanki, A (Nepal Journal of Obstetrics and Gynaecology, 2014)
We present a case of 23 years multigravid woman (G2P0+1) with chronic idiopathic thrombocytopenic purpura (ITP), refractory to treatment in forms of oral steroid, dapsone, azathioprine and splenectomy. She presented to the hospital in third trimester of pregnancy, with reduced platelet counts and purpuric rashes over abdomen and both upper extremeties. There was a past history of spontaneous abortion at 18 weeks. The patient responded to intravenous high dose methylprednisolone (HDMP) infusion leading to delivery of full term male baby. The baby also required treatment for thrombocytopenia with intravenous immunoglobulin (IVIG). This case lays down the importance of HDMP in form of using it effectively in managing acute crisis of low platelet counts in pregnant patients with ITP refractory to splenectomy. DOI: http://dx.doi.org/10.3126/njog.v9i1.11192 NJOG 2014 Jan-Jun; 2(1):64-66